Influence of air quality on the results of in vitro fertilization attempts: A retrospective study. (March 2017) - Carré, Julie; Gatimel, Nicolas; Moreau, Jessika; Parinaud, Jean; Leandri, Roger
Abstract: Objective: To assess the influence of air quality on the results of IVF. Study design: We performed a retrospective study on 292 patients who have undergone an IVF attempt from April 2012 to December 2015 in our French university hospital. Patients were included in the study if data on the air quality at home and at work were available and if they haven't been gone for more than 4 days in a month. Data were recorded during the 3 months before oocyte collection and 1 month after embryo transfer. Air quality measurements were obtained from the Observatoire Régional de l'Air en Midi-Pyrénées (ORAMIP) and concerned the levels of nitrogen dioxide (NO2 ), ozone (O3 ), particulate matter PM10 and SO2 measured every day. Results: Acute exposures to high levels NO2 or PM10 were associated with lower results of IVF (ovarian response to stimulation, number of top embryos) while these parameters were enhanced when patients were exposed to high levels of O3 during the first 2 months of folliculogenesis. These effects were found even for a short exposure (1 day). Conclusions: Air quality has an impact on global health and also on the reproductive function and public and authorities must be aware of environmental protection.